The Effect of Probiotic Provision on Ranum Handling in Broiler Chicken - I M., Supriana; Astawa, I P. A.; Mahardika, I G. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
This study aims to examine the digestibility of rations in broiler chickens that were given additional probiotics. Held in a cage owned by Mr. I Made Arcana, located in the village of Candikusuma, Jembrana, for 2 months and the Laboratory of Animal Nutrition at the Faculty of Animal Sciences, Udayana University for 1 week. The study was conducted using a Completely Randomized Design (CRD) consisting of four treatments, namely: treatment A (drinking water without the addition of probiotics as a control), treatment B (drinking water + probiotics 0.5 ml), treatment C (drinking water + probiotics 1 ml), and Treatment D (drinking water + 1.5 ml probiotics). Each treatment consisted of four replications and each test used 12 DOC CP 707 strains with an average body weight of 49.27 g. The variables observed were dry matter digestibility, organic matter digestibility, crude protein digestibility and crude fiber digestibility. The results showed that administration of probiotics through drinking water was 0.5 ml; 1 ml; 1.5 ml significantly (P <0.05) increased the digestibility of dry matter, crude protein, organic matter and crude fiber digestibility. Based on the results of this study concluded that the administration of probiotics through drinking water at the level of 0.5 ml; 1 ml; 1.5 ml can increase the digestibility of dry matter, digestibility of organic matter, digestibility of crude protein and digestibility of crude fiber in broiler chickens aged 5 weeks.   Keywords: Probiotics, broiler chicken, digestibility.